Reinventing EXARC, a Discussion between Members - Roeland P Paardekooper (EXARC Journal)
At the Annual General Meeting in Leiden (NL) in March 2016, about 25 EXARC members discussed future strategies for EXARC. We intend to collect opinions from members throughout 2016 and present a plan at the Annual General Meeting in 2017.